The Variation of Numeral Form Mean ‘one’ in Numeral Classifiers of the Batak Angkola Language - Nadra Nadra; Sri Wahyuni; Radhia Elita; Khofifah Aisyah Amini (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This paper aims to explain the variation of the numeral form, which means ‘one’ in the numeral classifier of the Batak Angkola language of Pintu Padang isolect and to describe the pattern of use of each of these forms. Data was collected by using observation and interview methods. Observation is done by listening to speakers communicate with each other. Interviews were conducted by directly asking three informants who met specific requirements and with several other sources. Data analysis was carried out using segmenting immediate constituents technique by dividing the lingual unit into numerals and classifiers. Based on the study results, it can be concluded that in the Batak Angkola language of Pintu Padang isolect found, ten variations of the numeral form, which means ‘one’ followed by a numeral classifier. The variation of the numeral form, which means ‘one’, is determined by the initial phoneme of the numeral classifier it follows in this case, the addition of a phoneme similar to or the same as the following phoneme. However, it is still limited to specific numeral classifiers. The numeral form still dominantly used is the form that has not experienced the addition of a phoneme.